Preparation of PTFE/PDMS superhydrophobic coating and its anti-icing performance. Issue 66 (23rd August 2017) - Ruan, Min; Zhan, Yanlong; Wu, Yuansheng; Wang, Xiangjie; Li, Wen; Chen, Yue; Wei, Maocai; Wang, Xiuzhang; Deng, Xiangyi
Abstract : The superhydrophobic coating was obtained from PTFE, DOTL, PDMS and TEOS on aluminum substrate. a–d present SEM images of coatings without PTFE, with 0.6 g, 1.0 g and 0.6 g PTFE after 34 times icing/deicing experiments, respectively. Abstract : Superhydrophobic surfaces with anti-icing performance have been the focus of research but few studies have reported an effective strategy that met the requirements of excellent mechanical properties and durability. In this article, superhydrophobic coatings were prepared from a mixture of superfine polytetrafluoroethylene powder, polydimethylsiloxane and tetraethyl orthosilicate through spin-coating on aluminum substrate followed by solidification at 150 °C. The static contact angle (CA) of the prepared coatings was as high as 163.6°. The surface morphology of the coatings was shown to be rough at micro/nano-scale with honeycomb microstructure, which allowed them to demonstrate excellent anti-icing properties. The experiments show that the superhydrophobic surface exhibits excellent mechanical abrasion resistance after mechanical abrasion against 1000 grit SiC sandpaper for 1.0 m at the applied pressure of 14.4 kPa. The surfaces CA remained unchanged after one month and decreased to be 140.0° after 34 subsequent icing/deicing experiments, which suggests good mechanical properties and durability of the prepared coatings. The present study may suggest a method for promising anti-icing applications in various fields.